KORELASI ANTARA MOTIVASI DENGAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN KELAS III SDN 34 - Asiry, Wedy Fazli; Uliyanti, Endang; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to analyze the correlation between motivation and learning outcomes of class III Citizenship Education public Elementary School 34 Central Pontianak. The variables in this study consist of independent variables (X), namely the motivation of students while the dependent variable (Y) is the learning outcomes of students in Civics Education lessons. This research uses descriptive method with a form of research that studies relationships. This study is a sample study with 64 people being the object of research taken using Probability sampling technique with a simple random sampling type Data collection techniques in this study is the indirect communication techniques and techniques of documentary studies. The results show the motivation of learners in public elementary school 34 in Central Pontianak classified is in excellent is 96.85%, and the learning outcomes of students in Civics Education lessons obtained an average value of 84.29 is very good because it is included in the range of 80-100 . The results of statistical calculations using the product moment correlation formula obtained the result of r count of 0,150 while r table 0,244 this means r count <r tebel or (0,150 <0,244) at 65% confidence level for N = 64. Based on the results of the study by using hypothesis testing the analysis of product moment motivation with student learning outcomes showed that the two variables did not have a positive correlation with the level of correlation including very low correlation.Â Keywords : Motivation, Learning Outcomes, Citizenship Education.